Gold‐Catalyzed Atroposelective Synthesis of 1, 1′‐Binaphthalene‐2, 3′‐diols. Issue 14 (23rd January 2020) - Zhang, Jianwei; Simon, Martin; Golz, Christopher; Alcarazo, Manuel
Abstract: A highly atroposelective (up to 97 % ee ) Au‐catalyzed synthesis of 1, 1′‐binaphthalene‐2, 3′‐diols is reported starting from a range of substituted benzyl alkynones. Essential for the achievement of high enantioselectivity during the key assembly of the naphto‐3‐ol unit is the use of TADDOL‐derived α‐cationic phosphonites as ancillary ligands. Preliminary results demonstrate that the transformation of the obtained binaphthyls into axially chiral monodentate phosphines is possible without degradation of enantiopurity. Abstract : Remote control : Two methyl groups strategically located at the backbone of the imidazolium component of a gold‐based catalyst are essential to deliver the desired binaphthol compounds in up to 97 % ee .